LEÓN ASSEMBLIES C.1188 AND COUNCIL AS A BASIS FOR SOCIAL STRUCTURE AND CIVIC PARTICIPATION. - Melo Carrasco, Diego; Gordo Molina, Ángel (Revista de Historia Social y de las Mentalidades, 2016)
1118 was the year when it was first officially recorded the attendance of elected men from each city to the royal assembly, along with the traditional groups which regularly participated in Leonese politics, which was since then conducted by Alfonso Ix. In regard to this historic landmark, we ask whether that record was indeed a reflection of those new men’s first actual participation in such kind of meeting called upon by the Leonese sovereign or, rather it was only the first time their attendance was documented, and they had already been participating in the on-going relationships between the crown and the rural communities. Analyzing the relationship between the king and the councils through the fuero, and examining the social bases that led to the peasant social organization, we were able to determine that elected council representatives had been referred to in a number of documents before and after Alfonso IX’s assembly. This finding suggests that the social base of the decision-making process had been broadened, and that from now on elected representatives became the main support of the Leonese monarchy’s actions.